Relações Entre Sentido de Vida, Bem-Estar e Ativismo LGBTQIAPN+ - Malavasi, Reziele Maria (2024)
The attitude of service towards someone or the feeling of belonging to something greater, such as a purpose, makes life meaningful. Contributing to the collective effort for equality and acceptance can provide LGBTQIAPN+ people with a broader sense of purpose, yet it can also lead to psychological distress in the face of daily stressors. The aim of this dissertation was to investigate whether greater engagement and/or willingness to participate in activist actions could represent a protective factor for the mental health of individuals engaged in such activities, being associated with higher levels of well-being through a sense of purpose, and lower levels of psychological disorders (e.g., anxiety, stress, depression). Methodologically, the dissertation consists of two complementary studies that generated two articles presented here. The first article is qualitative in nature, with online data collection using an open questionnaire to explore the motivations and impacts of activism on society and personal life through thematic analysis. To this end, 18 activists from Brazilian LGBTQIAPN+ Institutions participated, with an mean age of 37.3 years (SD=10.7). Results indicated purpose and the fight for rights as the main motivations for being an activist. Regarding perceived and experienced impacts, minority stress and Burnout appeared as possible consequences of the dedication expended. However, well-being was the greatest positive aspect reported, increasing through self-care, self-acceptance, group support, as well as being related to pleasure and satisfaction from the sense of purpose put into practice. The second article is quantitative in nature. In this study, 251 LGBTQIAPN+ people from all Brazilian regions participated, with an average age of 24.8 years (SD=6.6) and included the following instruments: Multidimensional Endogroup Identification Scale (MEIS), Activist Identity and Commitment Scale (AICS), Depression, Anxiety and Stress Scale (DASS-21), Inventory of Positive Psychological Functioning (IFPP), Purpose in Life Scale (EPV) and Sociodemographic Questionnaire for sample characterization. Descriptive and inferential analyzes were conducted to verify the correlation between the study variables, in addition to a confirmatory factor analysis for the activism scale, aiming for its validation. The results confirmed a unidimensional model for this instrument. Regarding inference and correlation results, activist individuals presented higher means on the ingroup scale, indicating a greater sense of belonging to a group than non-activist individuals. Positive correlations among the three dimensions of psychological suffering (anxiety, stress, and depression) were observed, and these variables were negatively associated with well-being (flourishing). The association between the constructs, tested through structural equation modeling, showed that ingroup identification is a significant predictor of activist identity, which in turn predicts well-being indirectly through the impact of purpose in life. Flourishing, in this model, is a significant predictor of depression levels in this population. This dissertation provides an important contribution to the development of interventions with LGBTQIAPN+ activists, aiming to reduce minority stress levels and promote well-being and quality of life through a sense of purpose.